PLIOCENE GRANITOID MASSIF IN THE KAZBEK VOLCANIC CENTER: FIRST GEOCHRONOLOGICAL AND ISOTOPE-GEOCHEMICAL DATA - Lebedev V.A.; Bubnov S.N.; Chernyshev I.V.; Gol'tsman Yu.V.; Chugaev A.V.; Vashakidze G.T. (My University, 2006)
The present paper is devoted to the geochronological and isotope–geochemical study of one of the reference (but insufficiently studied) terranes of young granitoid magmatism in the Kazbek neovolcanic area of the Greater Caucasus. Data obtained suggests the existence of a single intrusive massif in the area. They make it possible to determine its timing, major petrochemical characteristics of granitoids, and possible sources of magmatic melts.
Keywords: Kazbek; Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен